The Relationship between Fundamental Analysis and Stock Returns Using Panel Data: Evidence from Kompas 100 Indonesia - Dian S. P. Koesoemasari; Nirmala Nirmala; Isnaeni Rokhayati; Harsuti Harsuti; Untung Pamuji (Green Publisher Indonesia, 2023)
This research examines the significance of earnings per share, current ratio, debt equity ratio, return on equity and firm size on Kompas100 stock returns. The population in this study is companies listed on Kompas100 in 2016-2022, totalling 203 companies. The sampling method used in this research was purposive sampling, so that 28 companies were obtained. The analysis used in this research is panel data regression, and the selected regression model is the fixed effect. In this study it is proven that earnings per share, current ratio and firm size have a significant effect on stock returns while the debt equity ratio and return on investment have no significant effect. These findings provide an illustration that the company's fundamental conditions affect stock returns, then investors still have to take it into account in determining the selection of company shares to be purchased. These findings support signal theory and the efficient market hypothesis, investors need company fundamental information and think rationally in choosing stocks worth buying.